2013
DOI: 10.1213/ane.0b013e318288416d
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperglycemic Response to Major Noncardiac Surgery and the Added Effect of Steroid Administration in Patients With and Without Diabetes

Abstract: Treatment of intraoperative hyperglycemia should account for the hyperglycemic surgical stress response trend depending on the stage of surgery as well as the added effects of steroid administration. Denying steroid prophylaxis for postoperative nausea and vomiting for fear of hyperglycemic response should be reconsidered given the limited effect of steroids on intraoperative blood glucose concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 25 publications
4
42
1
1
Order By: Relevance
“…However, a single dose is not associated with any documented long-term complications. 13,14,18,19 We did not observe any complications in our study. The adverse effects of glucocorticoids are associated with prolonged use.…”
Section: Discussionsupporting
confidence: 37%
“…However, a single dose is not associated with any documented long-term complications. 13,14,18,19 We did not observe any complications in our study. The adverse effects of glucocorticoids are associated with prolonged use.…”
Section: Discussionsupporting
confidence: 37%
“…The patients receiving dexamethasone had a larger percentage increase as compared with the control group. These findings are also in concurrence with Abdelmalak et al 12 They observed an increase in the blood glucose concentrations (86 mg/dL) from the baseline values in patients given dexamethasone, as compared with (58 mg/dL) the patients who did not receive dexamethasone, all patients being nondiabetic. We observed that there is a rise in the blood glucose concentrations in group I patients, which began at 60 minutes and then increased further, but never beyond 200 mg/dL.…”
Section: Discussionsupporting
confidence: 90%
“…A plausible explanation is that patient response to insulin was masked by the hypermetabolic stress response to surgical tissue injury. Patients undergoing major non-cardiac surgery typically develop a profound perioperative stress response,[32] a reaction that is substantial, but highly variable. This systemic stress response which is associated with an increase in hepatic glucose production and worsened peripheral insulin resistance[33,34] may have exacerbated severe hyperglycemia and insulin unresponsiveness.…”
Section: Discussionmentioning
confidence: 99%